Unravelling the Mechanisms that Drive the Performance of Photocatalytic Hydrogen Production - Sergio San Martín (Catalysts, 2020)
The increasing interest and applications of photocatalysis, namely hydrogen production, artificial photosynthesis, and water remediation and disinfection, still face several drawbacks that prevent this technology from being fully implemented at the industrial level. The need to improve the performance of photocatalytic processes and extend their potential working under visible light has boosted the synthesis of new and more efficient semiconductor materials. Thus far, semiconductor–semiconductor heterojunction is the most remarkable alternative. Not only are the characteristics of the new materials relevant to the process performance, but also a deep understanding of the charge transfer mechanisms and the relationship with the process variables and nature of the semiconductors. However, there are several different charge transfer mechanisms responsible for the activity of the composites regardless the synthesis materials. In fact, different mechanisms can be carried out for the same junction. Focusing primarily on the photocatalytic generation of hydrogen, the objective of this review is to unravel the charge transfer mechanisms after the in-depth analyses of already reported literature and establish the guidelines for future research.